Visitors preferences on forest conservation and management in Endau-Rompin National Park - Matthew, N. K.; S, Ahmad; S, Ramachandran; Mohammad Afandi, Syamsul Herman; S, Zaiton (Forest Research Institute Malaysia, 2018)
Endau–Rompin National Park (ERNP) is an area of mega-microbial diversity and the second largest in Malaysia after Pahang National Park. The main objective of this study was to analyse users’ preferences and willingness-to-pay to enhance conservation and improve management of ERNP for sustainability. The discrete choice experiment was conducted on 350 local visitors to the national park who were purposely sampled. Results of a random parameter logit model for the choice experiment demonstrated that visitors placed highest values on the number of visitor’s arrival followed by biodiversity. The welfare measure for improvement in the management of the ERNP against the status quo was estimated at about RM37. This value was greater than the currently charged entrance fee of RM5. Hence, improvement in conservation and management would result in more value allotted by the visitors to the park. This study recommended that visitor entrance fees be revised to increase revenues for sustainable financing of conservation initiatives and, possibly, reduce congestion.